Scientific management of Phytophthora diseases in plantation crops - Chowdappa, P; Headge, Vinayaka (Indian Horticulture, 2019)
The coconut, arecanut and cocoa are grown in tropical high humid areas, where diseases caused by Phytophtora spp. are major constraints in their production. Fungicidal spray could control them only to a limited extent as heavy rains result in washing of fungicides from plant surfaces. An integrated disease management involving proper cultural practices, application of biocontrol agents, fungicidal sprays and host–plant resistance need to be employed for an effective management.